Preparation method and evaluation method of high-stability ferric oxide / graphene nano composite material

By loading iron oxide particles on graphene in nanomaterials, the problems of instability in nanomaterials and absorbance are solved, and good absorbance performance and stability are maintained over a wide concentration range, extending the service life of the material.

CN119542018AActive Publication Date: 2025-02-28KUNMING UNIV OF SCI & TECH

Patent Information

Application Number
CN202411714350.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The existing Fe2O3-containing nanomaterials have poor stability and unstable absorbance with concentration, resulting in a decrease in light absorption capacity or failure at higher or lower concentrations.

Method used

Using the preparation method of iron oxide/graphene nanocomposite, a multi-layer graphene solution was prepared by dissolving expanded graphite in DMF and ultrasonicating, and then adding FeCl3·4H2O and anhydrous sodium acetate for stirring to produce γ-type Fe2O3 particles and loading them on graphene. By reasonably designing the ratio of Fe2O3 adhesion to graphene of the material, good light absorption performance is maintained over a wide concentration range.

Benefits of technology

It improves the stability of nanomaterials in aqueous solution, enhances light absorption ability, makes the material's performance more stable in photothermal conversion, extends its service life, and maintains a significant absorbance function relationship at different concentrations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542018A_ABST
    Figure CN119542018A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and an evaluation method of a high-stability ferric oxide / graphene nano composite material, and relates to the technical field of nano materials. The preparation method comprises the following steps: dissolving expanded graphite in DMF (Dimethyl Formamide), standing for one night, carrying out ultrasonic treatment on a mixture in an ice bath environment for 2.5-3 hours, and adding water to prepare a multi-layer graphene solution; respectively weighing FeCl3. 4H2O and anhydrous sodium acetate, adding the FeCl3. 4H2O and the anhydrous sodium acetate into the multilayer graphene solution, and violently stirring to obtain a reaction precursor solution; carrying out heat preservation on the reaction precursor solution in a water bath, cooling to room temperature, and carrying out high-speed centrifugal separation to obtain a wet sample; and washing the wet sample with absolute ethyl alcohol and purified water, and drying to obtain reddish brown powder. The Fe2O3 particles are loaded on the graphene, the two-dimensional lamellar structure, high thermal conductivity and high dispersity of the graphene can effectively prevent agglomeration of the nano particles, uniform distribution of the particles is guaranteed, the stability of the nano material in an aqueous solution is improved, the light absorption capacity of the nano material is improved, and the performance of the material in photothermal conversion is more stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanomaterials, and in particular to a preparation method and an evaluation method of a high-stability iron oxide / graphene nanocomposite material. Background Art

[0002] γ type Fe 2 O 3 It is a ferromagnetic material with high magnetic permeability and magnetic saturation, which makes it widely used in magnetic materials and data storage devices. Due to its high surface activity, γ-type Fe 2 O 3 Often used as a catalyst or catalyst carrier. Under certain conditions, γ-Fe 2 O 3 Compared with α-Fe 2 O 3 More stable and not easily further oxidized or reduced. At the nanoscale, γ-Fe 2 O 3 The particles can exhibit superparamagnetism, which has potential applications in the biomedical field (such as magnetic resonance imaging contrast agents). However, the absorbance of nanomaterials is often unstable with changes in concentration, especially at higher or lower concentrations, due to problems such as particle agglomeration and sedimentation, the light absorption performance decreases significantly. At low concentrations, the content of nanomaterials in the solution is insufficient and the light absorption efficiency is low; at high concentrations, the interaction between particles is enhanced, and agglomerates are easily formed, resulting in a decrease in light absorption capacity or even failure. Therefore, it is urgent to develop a highly stable γ-Fe-containing nanoparticle. 2 O 3 The nanomaterial has a stable functional relationship between its absorbance and concentration, making it easy to select and use it based on its stability. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing a high-stability iron oxide / graphene nanocomposite material and an evaluation method thereof, so as to solve the existing problems of Fe 2 O 3 Nanomaterials have poor stability, especially the problem of unstable absorbance with concentration changes.

[0004] In order to solve the above technical problems, the present invention adopts the following technical solution: a method for preparing a high-stability iron oxide / graphene nanocomposite material, characterized in that it comprises the following steps:

[0005] S1. The expanded graphite was dissolved in DMF and allowed to stand overnight, the expanded graphite relative to DMF being 2.0 to 2.5 mg / ml;

[0006] S2. After ultrasonicating the mixture in step S1 for 2.5 to 3 hours in an ice bath, water was added to prepare a multilayer graphene solution;

[0007] S3. Weigh FeCl 3 ·4H 2 O and anhydrous sodium acetate are added to the multilayer graphene solution, and the solution is stirred vigorously at a speed of 500 to 600 r / min for 10 to 15 minutes to obtain a reaction precursor solution;

[0008] S4. The reaction precursor solution was kept in a water bath at 85 to 95° C. for 1.5 to 2 hours, cooled to room temperature and centrifuged at high speed to obtain a wet sample;

[0009] S5. The wet sample was washed with anhydrous ethanol and purified water and then dried to obtain a reddish brown powder.

[0010] A further technical solution is that the volume ratio of the amount of water added in step S2 to DMF is 1:4-5.

[0011] A further technical solution is that in step S3, FeCl 3 ·4H 2 O. The mass ratio of anhydrous sodium acetate to expanded graphite is 1.25-5:2.5-10:1.

[0012] A further technical solution is that after washing three times in step S5, the mixture is dried at 60-80° C. for 18-24 hours.

[0013] A further technical solution is that the reddish brown powder is γ-Fe 2 O 3 Nanocomposites with graphene.

[0014] A further technical solution is that the steps of analyzing the stability of the nanocomposite material are as follows:

[0015] (1) Prepare samples of different concentrations according to a concentration gradient and test their absorbance, and construct a functional relationship y=f(x) between absorbance x and concentration y by interpolation method;

[0016] (2) After the sample with the original concentration m is left to stand for a certain period of time, its absorbance is tested and the current concentration m is calculated based on the functional relationship. 0 , at this time the stability of the sample n = m 0 / m, the larger the n value, the higher the sample stability.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] 1. The present invention prepares a multilayer graphene solution by dissolving expanded graphite in DMF and then ultrasonically treating the solution in an ice bath, and then adding FeCl 3 ·4H 2O and anhydrous sodium acetate are stirred vigorously, and the iron salt is hydrolyzed in water to generate Fe(OH) 3 With hydrogen ions, anhydrous sodium acetate hydrolyzes to generate acetic acid molecules and hydroxide ions. Acetate ions adjust the pH value, maintain an alkaline environment and weaken particle aggregation, which is beneficial to the γ-type Fe2O 3 The rapid formation and aggregation of iron ions and high-speed stirring produce more γ-type Fe 2 O 3 The precursor solution is fully mixed by sufficient stirring, and the target product can be obtained by heating it in a water bath at 90°C for 2h, which simplifies the reaction.

[0019] 2. The present invention is achieved by 2 O 3 The particles are loaded on graphene. The two-dimensional sheet structure, high thermal conductivity and high dispersibility of graphene can effectively prevent the agglomeration of nanoparticles, ensure the uniform distribution of particles, improve the stability of nanomaterials in aqueous solutions, improve the light absorption capacity of nanomaterials, make the material's performance in photothermal conversion more stable, and extend its service life.

[0020] 3. The present invention rationally designs the Fe 2 O 3 The ratio of the amount of attachment and graphene can maintain good light absorption performance in a wide concentration range, ensuring that the functional relationship of the material's absorbance at different concentrations is more significant. In particular, at higher concentrations, the material's absorbance shows a gradual increase trend, and the agglomeration effect is small. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 For graphene, Fe in Example 1 2 O 3 and γ-Fe 2 O 3 SEM and EDS images of graphene / graphene nanocomposites.

[0022] Figure 2 The γ-Fe prepared in Example 1 2 O 3 XRD diffraction patterns of graphene nanocomposites.

[0023] Figure 3 In the embodiment, γ-Fe 2 Electron microscope and EDS images of O attached to graphene.

[0024] Figure 4 This is a graph showing the sedimentation of the sample over time.

[0025] Figure 5 This is the relationship between sample concentration and stability. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0027] Example 1

[0028] 1) Weigh 0.5 g of expanded graphite and dissolve it in 200 ml of DMF solution and let it stand overnight.

[0029] 2) After the solution was sonicated for 180 min (the solution was kept in an ice bath and the liquid level was ensured to be higher than the solution level), 50 ml of water was added to prepare a multilayer graphene solution.

[0030] 3) Weigh 0.625g FeCl 3 ·4H 2 O and 1.25 g of anhydrous sodium acetate were added to the multilayer graphene solution, and the solution was vigorously stirred at a speed of 500 r / min for 10 min to obtain a reaction precursor solution.

[0031] 4) Place the reaction precursor solution in a water bath at 90°C for 2 hours. To ensure sufficient reaction, the water bath liquid level must be higher than the solution level.

[0032] 5) The solution after the reaction was cooled to room temperature and then placed in a high-speed centrifuge for separation to obtain a wet sample, which was then washed three times with anhydrous ethanol and purified water. The washed sample was dried at 60° C. for 24 h to obtain a reddish-brown powder sample G1.

[0033] Example 2

[0034] 1) Weigh 0.5 g of expanded graphite and dissolve it in 200 ml of DMF solution and let it stand overnight.

[0035] 2) After the solution was sonicated for 180 min (the solution was kept in an ice bath and the liquid level was ensured to be higher than the solution level), 50 ml of water was added to prepare a multilayer graphene solution.

[0036] 3) Weigh 1.25g FeCl 3 ·4H 2 O and 2.5 g of anhydrous sodium acetate were added to the multilayer graphene solution, and the solution was vigorously stirred at a speed of 500 r / min for 10 min to obtain a reaction precursor solution.

[0037] 4) Place the reaction precursor solution in a water bath at 90°C for 2 hours. To ensure sufficient reaction, the water bath liquid level must be higher than the solution level.

[0038] 5) The solution after the reaction was cooled to room temperature and then placed in a high-speed centrifuge for separation to obtain a wet sample, which was then washed three times with anhydrous ethanol and purified water. The washed sample was dried at 60° C. for 24 h to obtain a reddish-brown powder sample G2.

[0039] Example 3

[0040] 1) Weigh 0.5 g of expanded graphite and dissolve it in 200 ml of DMF solution and let it stand overnight.

[0041] 2) After the solution was sonicated for 180 min (the solution was kept in an ice bath and the liquid level was ensured to be higher than the solution level), 50 ml of water was added to prepare a multilayer graphene solution.

[0042] 3) Weigh 1.875g FeCl 3 ·4H 2 O and 3.75 g of anhydrous sodium acetate were added to the multilayer graphene solution, and the solution was vigorously stirred at a speed of 500 r / min for 10 min to obtain a reaction precursor solution.

[0043] 4) Place the reaction precursor solution in a water bath at 90°C for 2 hours. To ensure sufficient reaction, the water bath liquid level must be higher than the solution level.

[0044] 5) The solution after the reaction was cooled to room temperature and then placed in a high-speed centrifuge for separation to obtain a wet sample, which was then washed three times with anhydrous ethanol and purified water. The washed sample was dried at 60° C. for 24 h to obtain a reddish-brown powder sample G3.

[0045] Example 4

[0046] 1) Weigh 0.5 g of expanded graphite and dissolve it in 200 ml of DMF solution and let it stand overnight.

[0047] 2) After the solution was sonicated for 180 min (the solution was kept in an ice bath and the liquid level was ensured to be higher than the solution level), 50 ml of water was added to prepare a multilayer graphene solution.

[0048] 3) Weigh 2.5g FeCl 3 ·4H 2 O and 5 g of anhydrous sodium acetate were added to the multilayer graphene solution, and the solution was vigorously stirred at a speed of 500 r / min for 10 min to obtain a reaction precursor solution.

[0049] 4) Place the reaction precursor solution in a water bath at 90°C for 2 hours. To ensure sufficient reaction, the water bath liquid level must be higher than the solution level.

[0050] 5) The solution after the reaction was cooled to room temperature and then placed in a high-speed centrifuge for separation to obtain a wet sample, which was then washed three times with anhydrous ethanol and purified water. The washed sample was dried at 60° C. for 24 h to obtain a reddish-brown powder sample G4.

[0051] refer to Figure 1 , Figure 1 (a) shows the SEM image of the self-made multilayer graphene in Example 1. The graphene has a sheet-like structure with a large number of specific wrinkles on the surface. Some layers are interconnected to form a three-dimensional network framework. This sheet structure and wrinkles are the basis for the subsequent Fe 2 O 3 The attachment of particles provides abundant surface active sites and helps prevent the agglomeration of nanoparticles.

[0052] Figure 1 (b) shows Fe 2 O 3 SEM image of Fe nanoparticles. 2 O 3 The particles are spherical nanoparticles with a particle size between 6nm and 10nm. However, due to the van der Waals force between nanoparticles and their inherent magnetic effects, Fe 2 O 3 The particles tend to agglomerate into larger clusters with sizes ranging from 200nm to 500nm.

[0053] Figure 1 (c) shows that γ-Fe 2 O 3 SEM image of the Fe / graphene nanocomposite. 2 O 3 The particles are evenly attached to the surface of multilayer graphene. 2 O 3 , the agglomeration of particles in the composite material is significantly reduced. Small particles with a diameter of about 10nm are dispersed on the graphene surface. These particles are combined with graphene through molecular forces to form a stable structure, which ensures the dispersion and photothermal conversion performance of the material.

[0054] Figure 1 (d) is γ-Fe 2 O 3 A partial magnified image of the graphene nanocomposite. The magnified image further shows the dispersed small particles of γ-Fe 2 O 3 (diameter is about 10nm) uniformly covers the graphene surface, indicating that the Fe 2 O 3 The particle agglomeration phenomenon has been significantly improved. At the same time, some small agglomerates with a size ranging from 80nm to 200nm appeared on the surface, which are presumably the result of excessive generation of γ-Fe 2 O 3 The particles are adsorbed on the graphene surface.

[0055] Figure 1 (e) is γ-Fe 2 O 3 Energy dispersive spectroscopy (EDS) analysis of graphene nanocomposites shows the types of elements in the sample, and it can be seen that the main elements in the sample are C, O, and Fe, which is consistent with the preparation process of the present invention.

[0056] refer to Figure 2 The XRD diffraction pattern of the product in Example 1 further verified that γ-Fe 2 O 3 The structure and chemical composition of graphene nanocomposites are shown in the figure. The diffraction peaks of the graphene curve at 26.3°, 42.2°, 44.3° and 54.5° correspond to the (002), (100), (101) and (004) crystal planes, indicating that they are the diffraction peaks of graphene (JCPD Card 41-1487). 2 O 3 The diffraction peaks at 30°, 35.4°, 43°, 56.9° and 62.5° of the curve correspond to the (220), (311), (400), (511) and (440) crystal planes, indicating that they are the diffraction peaks of magnetite (JCPD Card 19-0629).

[0057] The diffraction peaks of the composite material curve at 26.3°, 42.2°, 44.3° and 54.5° are the diffraction peaks of Graphene (JCPDCard41-1487) corresponding to its (002), (100), (101) and (004) crystal planes. The diffraction peaks at 30°, 35.4°, 43°, 56.9° and 62.5° are the diffraction peaks of magnetite (JCPD Card 19-0629) corresponding to its (220), (311), (400), (511) and (440) crystal planes. In addition to the diffraction peaks of these two phases, no other impurity peaks are obviously observed, indicating that the prepared composite material is γ-Fe2O3 with high purity.

[0058] refer to Figure 3 , Figure 3 Fe in G1-G4 2 O 3 Electron microscopy and EDS images attached to graphene sheets. As shown in Figure (a), G1 has almost no large aggregates, and Fe 2 O 3 The particles are evenly distributed on the graphene sheet. G2(b) has a small amount of Fe compared to G1. 2 O 3Small aggregates, the size of the aggregates is about 100nm. The surface of G3 (c) is covered with Fe 2 O 3 There are also many aggregates on the surface, and the size of the aggregates is between 100-150nm. 2 O 3 The particles are completely filled, and the size of the agglomerates increases further, ranging from 200 to 300 nm, which is close to Figure 1 (b) Medium-pure Fe 2 O 3 The size of the nanoparticles. This is due to the 2 O 3 After the graphene sheet is fully attached, Fe 2 O 3 Due to the inherent magnetism between magnetic particles, the particles will adsorb each other, resulting in a large number of agglomerations on the graphene surface. Table 2 is the EDS component analysis results. It can be seen from the table that as the proportion of iron source increases, the iron and oxygen elements gradually increase, and the carbon element gradually decreases. This is consistent with the SEM analysis results, that is, from G1 to G4, on the same mass of graphene sheets, Fe 2 O 3 The amount of Fe attached gradually increased, and large particles of Fe gradually appeared. 2 O 3 Agglomerates may change the thermophysical properties of the sample.

[0059] Table 2

[0060]

[0061] Example 5

[0062] In order to study the stability of samples G1-G4, different mass concentrations of γ-Fe 2 O 3 The aqueous solution of the / Graphene composite nanomaterial was left at room temperature for 7 days to observe its sedimentation. Figure 4 As shown, the color of the composite nanomaterial becomes significantly lighter after standing for 7 days, indicating that some larger nanoparticle agglomerates have precipitated, reducing the solid content in the base liquid, which will affect the optical absorption properties of the nanofluid.

[0063] For further quantitative analysis, ultraviolet spectrophotometry and observation methods were used to analyze and evaluate the stability of the nanocomposite material. The specific steps are as follows:

[0064] (1) Prepare samples of different concentrations according to a concentration gradient and test their absorbance, and construct a functional relationship y=f(x) between absorbance x and concentration y by interpolation method;

[0065] For the G1 sample, 50 ppm was used as the starting point and 50 ppm as the concentration gradient. The absorbance of 9 samples with concentrations ranging from 50 to 500 ppm was tested, and the functional relationship between the absorbance x and the concentration y was obtained by fitting based on the interpolation method.

[0066] According to the above method, G2, G3, and G4 are tested in the same way, and the obtained functional relationship is as follows:

[0067] G1: y = 8x 2 +145x+13

[0068] G2: y = 60x 2 +30x+60

[0069] G3: y = 21x 2 +120x+8

[0070] G4: y = -3x 2 +175x+17

[0071] (2) After the sample with the original concentration m is left to stand for a certain period of time, its absorbance is tested and the current concentration m is calculated based on the functional relationship. 0 , at this time the stability of the sample n = m 0 / m, the larger the n value, the higher the sample stability.

[0072] Depend on Figure 5 As shown, with Fe 2 O 3 With the increase of the amount of adhesion, the stability of the nanocomposite materials of each sample first increases and then decreases. The stability of the G1 sample is the worst at a lower concentration. The concentration of the 100ppm and 200ppm samples drops below 30% after standing for 7 days, reaching a peak of 43.87% at 300ppm. The stability of the G2 sample is the best compared with other samples, reaching a maximum value of 75.88% at 100ppm, and the stability of the nanocomposite material decreases with the increase of mass concentration, reaching a minimum value of 35.84% at 400ppm. The stability of G3 is least affected by concentration, and the stability variance after 7 days is about 8.772.

[0073] Although the present invention is described herein with reference to a number of illustrative embodiments of the present invention, it will be appreciated that those skilled in the art may devise numerous other modifications and implementations that fall within the scope of the present disclosure. More specifically, within the scope of the present disclosure, drawings, and claims, a variety of variations and modifications may be made to the components or layout. In addition to variations and modifications to the components or layout, other uses will be apparent to those skilled in the art.

Claims

1. A method for preparing a high-stability iron oxide / graphene nanocomposite material, characterized in that: The steps include: S1. The expanded graphite was dissolved in DMF and allowed to stand overnight, the expanded graphite relative to DMF being 2.0 to 2.5 mg / ml; S2. After ultrasonicating the mixture in step S1 for 2.5 to 3 hours in an ice bath, water was added to prepare a multilayer graphene solution; S3. Weigh FeCl3·4H2O and anhydrous sodium acetate respectively, add them to the multilayer graphene solution, stir vigorously at a speed of 500 to 600 r / min, and stir for 10 to 15 minutes to obtain a reaction precursor solution; S4. The reaction precursor solution was kept in a water bath at 85 to 95° C. for 1.5 to 2 hours, cooled to room temperature and centrifuged at high speed to obtain a wet sample; S5. The wet sample was washed with anhydrous ethanol and purified water and then dried to obtain a reddish brown powder.

2. The method according to claim 1, characterized in that: The volume ratio of water added to DMF in step S2 is 1:4-5.

3. The method according to claim 1, characterized in that: In step S3, the mass ratio of FeCl3·4H2O, anhydrous sodium acetate and expanded graphite is 1.25-5:2.5-10:

1.

4. The method according to claim 1, characterized in that: In the step S5, the mixture is washed three times and then dried at 60 to 80° C. for 18 to 24 hours.

5. The method according to claim 1, characterized in that: The reddish brown powder is a nanocomposite material of γ-Fe2O3 and graphene.

6. The method according to claim 1, characterized in that: The steps of analyzing the stability of the nanocomposite material are as follows: (1) Prepare samples of different concentrations according to a concentration gradient and test their absorbance, and construct a functional relationship y=f(x) between absorbance x and concentration y by interpolation method; (2) After the sample with an original concentration of m is left to stand for a certain period of time, its absorbance is tested and the current concentration m0 is calculated based on the functional relationship. At this time, the stability of the sample is n = m0 / m. The larger the n value, the higher the sample stability.

Citation Information

Patent Citations

  • Preparation method of magnetic Fe2O3 nanoparticles as well as method for compounding magnetic Fe2O3 nanoparticles with nano-carbon material

    CN108249482A

  • Preparation method of alpha-type fe_2O_3 nanoparticles / multilayer graphene composite material

    CN109243832A

  • Preparation of magnetic porous graphene and rapid detection method of low-concentration triclosan in water by employing magnetic porous graphene

    CN109932449A

  • Iron carbide material, manufacturing method thereof, and magnet

    JP2014207341A

  • Non-covalent magnetic graphene oxide composite material and method of production thereof

    WO2016172755A1

Cited By

  • Preparation method of composite photothermal conversion material based on hot pasting waste powder

    CN120268066A